PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA PERSONEL SATSABARA POLRES SAMPANG KABUPATEN SAMPANG - jurnalmap map; Kamarul Hidayat (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This research was conducted at the Sampang District Police, Sampang Regency. The total sample size was 36 personnel. The aim is to describe the transformational leadership and transactional leadership research that has a partial and significant effect on the performance of the personnel of the Satsabara Police, Sampang District, Sampang Regency. Then to prove whether transformational leadership and transactional leadership have a both simultaneous and partially significant effect on the performance of the Satsabara personnel at the Sampang District Police, Sampang Regency. This type of research is an explanatory study using a quantitative research approach. The results showed that simultaneously, transformational leadership and transactional leadership have a very significant influence on the performance of personnel in the Sampang Police, Sampang Regency. Partially, transformational leadership and transactional leadership have a significant influence on personnel performance at the Sampang Police, Sampang Regency. Thus, it can be said that all the independent variables partially have a significant effect on the performance of personnel at the Sampang Police, Sampang Regency. Keywords: transformational leadership, transactional leadership, personnel performance